(untitled) (National Administration Journal, 2025)
The work proposes the structuring of the concept of Neuroquantum Marketing, based on the link of the neural management of consumer data and in direct relation to the precepts of Quantum Mechanics, pointing out the theoretical and hypothetical applications usable through management models of administration and commercial development, specifying at the same time the quantum foundations in the use of data and behavioral patterns of customers. allowing to detail aspects such as quantum entanglement, indeterminacy, wave superposition and others of a similar nature, reaching elementary points of traditional Marketing, thus specifying the foundations for an eventual model of Quantum Marketing based on neural data, and linked to the indeterministic management of people’s behavior and their commercial decision, all based on the application of quantum structural principles to the professional management of business marketing.